Effect of molecular targeted agents in chemotherapy for treating platinum-resistant recurrent ovarian cancer: A systematic review and meta-analysis. Issue 32 (13th August 2021) - Liu, Luting; Xiong, Wanchun
Abstract : Abstract: This study aimed to investigate the effect of molecular targeted agents (MTAs) in chemo on platinum-resistant recurrent ovarian cancer (ROC). We performed this meta-analysis according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statements. Randomized controlled trials reporting data about platinum-resistant ovarian cancer treated by MTAs were included. The endpoints for the present study included overall survival and progression-free survival. We analyzed 9 randomized controlled trials including 3631 patients with ROC. The pooled analysis indicated that a combination of MTAs with chemo could markedly increase objective response rate in those patients ( P = .012). Nevertheless, the survival rate of those patients was not markedly changed ( P = .19). Besides, the combination of MTAs with chemo dramatically aggravated the occurrence of adverse events ( P < .05). Moreover, it resulted in the termination of treatment ( P = .044) in those patients, but it had no effect on fatal adverse events ( P = .16). Our results indicated that the combination of MTAs with chemo notably improved objective response rate in patients with platinum-resistant ROC, but its benefit did not translate into survival benefits. Abstract : Supplemental Digital Content is available in the text